Deutsch; Ein Lehrbuch fur Auslander: Texte und Ubungen: Mathematik, Physic, Chemie, Biologie - Fiedler M. Martin; Fritz J. Johannes; HeBler J. Jutta; Hubener K. Kurt; Kistner R. Rolf; Mockel W. Werner (Karl-marx-Universitat)
Авт. указ. на обороте тит. л.